1974
DOI: 10.1055/s-0028-1098602
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Retrograde Cholangiopancreatography in the Diagnosis of Pancreatic Cancer: Experiences with 54 Cases

Abstract: Pathological alterations of the ductal system found during ERCP in 1082 examinations were due to pancreatic carcinoma in 54 patients. The diagnosis was confirmed by laparotomy or autopsy. Predominant findings in 42 patients were stenoses, prestenotic dilatation, caliber variation, stop of contrast medium and ductal displacement in pancreatography. In 28 cholangiograms stenoses were most common which were localized in one third of the cases in the proximal common bile duct. Four types may be differentiated: a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1975
1975
1998
1998

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Stadelman et al (83) reported that predominant findings in 42 patients with pancreatic carcinoma examined by ERCP were stenosis, prestenotic dilatation, caliber variation, hold up of contrast medium and ductal displacement in pan creatography, and that in 28 cholangiograms in these patients stenoses were found in one third of the cases in the proximal common bile duct. They classi fied findings of pancreatic carcinoma into four types: a stenosing type, an obstructed type, a tapering type and a cavernous type, and the stenosing type was divided in a form with and without interruption of the contrast medium column.…”
Section: Classification O F the Lesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stadelman et al (83) reported that predominant findings in 42 patients with pancreatic carcinoma examined by ERCP were stenosis, prestenotic dilatation, caliber variation, hold up of contrast medium and ductal displacement in pan creatography, and that in 28 cholangiograms in these patients stenoses were found in one third of the cases in the proximal common bile duct. They classi fied findings of pancreatic carcinoma into four types: a stenosing type, an obstructed type, a tapering type and a cavernous type, and the stenosing type was divided in a form with and without interruption of the contrast medium column.…”
Section: Classification O F the Lesionmentioning
confidence: 99%
“…Pathological changes in chronic pancreatitis were usually diffuse, whereas localized severe changes were observed in carcinoma (41). Stadehnann et al (83) thought that a precise differential diagnosis between pancreatic carcinoma and chronic pancre atitis was not possible but a long stenosis with or without hold-up of the con trast medium spoke in favor of a tumorous process. Trapnell (85) reported that both a uniform dilatation of the duct system, and gap between the head of the dye and the duodenum in pancreatogram may be taken as indicative of the presence of a carcinoma of the head of the pancreas, hence allow an immediate distinction between this condition and chronic relapsing pancreatitis.…”
Section: Diagnosis With Pancreatic Carcinomamentioning
confidence: 99%
“…The use of miniprobes in the pancreatic and bile ducts may increase diagnostic accuracy even further and would be useful in differentiating cholangiocarcinoma from pancreatic cancer [2]. Despite these advanced techniques for the diagnosis of pancreatic carcinoma, the majority of patients still present late, and the rate of resectability is low [14,17]. A normal pancreatogram in this study did not equate with earlier presentation.…”
Section: Discussionmentioning
confidence: 64%
“…Some authors have stressed the overlapping spectrum of ductal changes in pancreatic cancer and chronic pancreatitis. They have reported lower figures [10,16,17], although serum tumor markers, in particular CA 19-9, can now satisfactorily discriminate between these two conditions [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation